Synthesis and Pharmacology of Clinical Drugs Containing Isoindoline Heterocycle Core - Mukund Jha; Dani Youssef; Haley Sheehy; Amitabh Jha (Organics)
Heterocyclic compounds are the cornerstone for active pharmaceutical ingredients. Among heterocycles, isoindoline core occupies a special place, as ten commercial bioactive compounds/drugs contain this skeleton decorated with several functional groups required for optimal receptor binding. These drugs are employed for indications such as multiple myeloma, leukemia, inflammation, hypertension, edema, obesity, and insect control. This review presents the pharmacological activities, mechanisms of action, and chemical syntheses of these commercial bioactive molecules/drugs.